Design, synthesis, and biological evaluation of BRD4 degraders. (15th January 2023) - Ding, Mengyuan; Shao, Yingying; Sun, Danwen; Meng, Suorina; Zang, Yi; Zhou, Yubo; Li, Jia; Lu, Wei; Zhu, Shulei
Graphical abstract: Highlights: Compound 8b exhibited excellent antiproliferative activity on MM.1S (IC50  = 27 nM) and MV-4-11 (IC50  = 3 nM) cell lines. Compound 8b significantly induced the degradation of BRD4 protein. Compound 8b could effectively block the activation of MRC5 cells by inducing the degradation of BRD4 protein. Abstract: Epigenetic proteins are one of the important targets in the current research fields of cancer therapy. A family of bromodomain-containing (BRD) and extra terminal domain (BET) proteins act as epigenetic readers to regulate the expression of key oncogenes and anti-apoptotic proteins. Recently, although BET degraders based on PROTAC technology have achieved significant antitumor effects, the lack of selectivity for BET protein degradation has not been fully addressed. Herein, a series of small molecule BRD4 PROTACs were designed and synthesized. Most of the degraders were effective in inhibiting MM.1S and MV-4-11 cell lines, especially in MV-4-11. Among them, degrader 8b could induce the degradation of BRD4 and exhibited a time- and concentration-dependent depletion manner and there was a significant depletion of BRD4, laying a foundation for effectively treating leukemia and multiple myeloma. Moreover, 8b could also effectively prevent the activation of MRC5 cells by inducing the degradation of BRD4 protein, which preliminarily proves that the BRD4 degrader based on the PROTAC concept has great potential for the treatment of pulmonary fibrosis. Taken together, these findings laid a foundation for BRD4 degraders as an effective strategy for treating related diseases.